Climate Change and its Effect on Human Society - Siva Vemula, Rama (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Due to extreme weather events and vector-borne diseases like malaria and dengue fever spreading, climate change poses an increasing threat to public health. While climate change will have a global impact on health, the effects will be unevenly distributed. In accordance with the Third Assessment Report, climate change vulnerability is a result of susceptibility to climate change, sensitivity to climate change, and adaptation to climate change (Intergovernmental Panel on Climate Change-2001). According to the World Health Organization, people are more vulnerable in developing countries, especially on small islands, in deserts, steep mountains, and coastal areas with dense populations. India is a huge developing country bordered on the north by the Great Himalayas, which contain the third greatest mass of ice on the planet, and on the south by a densely populated seashore. 700 million of the country's one billion rural residents are dependent on climate-sensitive areas (agriculture, forestry and fisheries), as well as on the country's natural resources (water and biodiversity) (including mangroves, coastal areas, and grasslands) for their very survival. Heatwaves, flooding (both on land and at the coast), and severe winds are all frequent occurrences. Malaria, starvation, and diarrhea are all serious health problems. Increased weather-related disasters and adverse health outcomes could wreak havoc on the country's already-fragile health system. As a result, the problem requires rapid resolution. To protect public health from the effects of climate change, both mitigation and adaptation are required. Climate change risks can be considerably reduced if the two work together.
Keywords: Climate change; health effects; India; public health